CORPORATE SOCIAL RESPONSIBILITY, ECONOMIC VALUE ADDED, ENTERPRISE RISK MANAGEMENT, AND FINANCIAL PERFORMANCE: INTELLECTUAL CAPITAL MODERATION - Savitri, Enni (Universitas Brawijaya, Indonesia, 2022)
Financial performance is required to evaluate possible economic resource changes and forecast the existing resources' production potential. This study examines how intellectual capital acts as a buffer between the effects of corporate social responsibility, economic value-added, and pricing risk management on financial performance. The 52 manufacturing enterprises that were listed on the Indonesia Stock Exchange between 2016 and 2020 made up the study's population. Purposive sampling was utilized during sampling. Manufacturing businesses in the consumer goods sector that consistently disclose an exhaustive annual report meet the sample criteria. Based on these standards, 39 businesses were selected for the sample. The method of data processing employs moderate regression analysis (MRA). The findings demonstrated that enterprise risk management, economic value-added, and corporate social responsibility impacted financial performance. The impact of corporate social responsibility on financial performance is strengthened by intellectual capital. The influence of economic value addition and the impact of enterprise risk management on financial performance is strengthened by intellectual capital. The innovative aspect of this study is the non-monetary IC index, which measures intellectual capital.